2014
DOI: 10.1021/jp502391e
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Apparent Crystal Structure of a Highly Faulted UPRM-5 Type Flexible Porous Titanium Silicate via a Polymorph Based Superposition Model, a Rietveld Refinement and a Pair Distribution Function

Abstract: The crystal structure of a UPRM-5 titanium silicate prepared using tetraethylammonium (TEA + ) has been approximated using a superposition model product of a polymorph stacking and a dual-phase Rietveld refinement method. Na + -UPRM-5 polymorphs were employed to elucidate the level of polymorphism or faulting in the crystal structure. DIFFaX simulations revealed that it was impossible to match the experimental diffraction data based solely on "pure" polymorphs. Instead, an intergrowth of combinations of polymo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…A set of diffraction patterns gathered from 30 to 300 °C is shown in Figure . Unit cell parameters for both Sr 2+ -UPRM-5 variants are shown in Table S1 in Supporting Information and corresponded to an orthorhombic symmetry, which correlates well with the results recently reported for the crystal refinement of Na + -UPRM-5 prepared with TEA + . The structure and faulting in this variant were described via stacking of orthorhombic and triclinic polymorph phases, but the former is the predominant one (90%).…”
Section: Resultssupporting
confidence: 85%
See 4 more Smart Citations
“…A set of diffraction patterns gathered from 30 to 300 °C is shown in Figure . Unit cell parameters for both Sr 2+ -UPRM-5 variants are shown in Table S1 in Supporting Information and corresponded to an orthorhombic symmetry, which correlates well with the results recently reported for the crystal refinement of Na + -UPRM-5 prepared with TEA + . The structure and faulting in this variant were described via stacking of orthorhombic and triclinic polymorph phases, but the former is the predominant one (90%).…”
Section: Resultssupporting
confidence: 85%
“…As reported recently for Sr 2+ -UPRM-5 prepared using TEA + , these materials have a set of two accessible pore channels each with different dimensions . Adsorption studies made for ETS-4, which also contains a bimodal pore system, have shown that this feature results in poor prediction of adsorption–desorption diffusivities when traditional phenomenological transport models are employed. , The narrower channels in UPRM-5 correspond to the 8-MR pore system previously mentioned, which is characteristic of flexible titanium silicates. ,, The other dominant pore system is a result of the structural faulting, which is controlled by the choice of SDA and effectively results in larger pore dimensions . Per the discussion of the XRD results, the 8-MR pores or channel system in Sr 2+ -UPRM-5 (TPA) and Sr 2+ -UPRM-5 (TBA) seems to be the most affected by thermal contraction during thermal activation.…”
Section: Resultsmentioning
confidence: 87%
See 3 more Smart Citations